Hepatitis C Virus Therapy for Decompensated and Posttransplant Patients. Issue 3 (March 2017) - Dailey, Francis; Ayoub, Walid S.
Abstract : Treatment of hepatitis C (HCV) has been revolutionized with the introduction of the direct-acting antivirals (DAA). The DAAs allowed patients to better tolerate HCV therapy with much lower side effects and better efficacy. The DAA also offered hope for a cure in HCV patients who cannot tolerate interferon-based therapy. Such populations include patients with decompensated cirrhosis and postliver transplantation. Despite DAA therapy showing cure rate of over 95% in the absence of cirrhosis, cure rate in the decompensated liver disease setting remains lower. In this paper, we aim to review the current recommendations for the treatment of HCV in patients with decompensated cirrhosis and postliver transplantation.